La comprensión de textos expositivos en estudiantes del quinto grado de primaria de la Institución Educativa N° 60756 Claverito, Iquitos 2021 - Flores Perez, Jose Manuel (2022)
The objective of this study was to describe the level of achievement of the comprehension of expository texts in the students of the fifth grade of primary education of the Educational Institution No. 60756 Claverito, Iquitos, 2021. This research is of a descriptive type, with a quantitative approach. The simple descriptive design Ox, y was used. The population consisted of 140 students. The sample was 80 students, 20 for each section of the fifth grade. To measure the level of achievement of the comprehension of expository texts, the questionnaire instrument was used. The results obtained indicate that "The level of achievement of the comprehension of expository texts is at the beginning in the majority of the students (50.0%) of the fifth grade of primary education of the Educational Institution No. 60756 Claverito, Iquitos, 2021, and they reach an average of 10.2 points. Regarding the literal, inferential and critical dimensions, in the first they reach an average of 9.5; in the last two the average is 11 and 9 points respectively. It is concluded that the learning of the comprehension of expository texts is not developed at acceptable levels in the fifth grade students of the Educational Institution No. 60756 Claverito, Iquitos, 2021.